Photostabilization of Poly (Vinyl Chloride) by Some Schiff Base Derivedfrom 2-amino pyridine - Nief, Olfa A (Al-Nahrain Journal of Science, 2018)
In this paper, Schiff bases (1-6) were prepared and synthesized by condensing aromatic aldehydes (benzaldehyde, salicylaldehyde,-methoxylbenzaldehyde, -hydroxybenzaldehyde, furfural and isatin) with 2-amino pyridine. Spectrophotometric (FTIR) and (UV.VIS) and elemental analysis (CHN) techniques have been employed for the characterization of the additives. All the additives were used as photostabilizer for poly (vinylchloride). The rate of photodegradation and photostabilization of PVC films (40µm) were monitored with irradiation time by measuring the carbonyl (Ico) and polyene (Ipo) indices values (the concentration of additives kept constant at 0.3% wt/wt). The light of wave length 313nm is used for irradiation of polymer films at temperature around 40oC.The effect of additives concentration range from (0.1-0.5) wt% on the rate of photodegradation and photostabilization was also monitored for PVC films. The rates increase when additives concentration is increased. The effect of film thickness is also studied and results show that increasing film thickness will decrease the rate of photo degradation in the following sequence:[2] > [5] > [4] > [6] > [3] > [1]> PVCAccording to the experimental results several mechanisms were suggested depending on the structure of the additive.